2005
DOI: 10.1242/dev.01671
|View full text |Cite
|
Sign up to set email alerts
|

thick tassel dwarf1encodes a putative maize ortholog of theArabidopsis CLAVATA1leucine-rich repeat receptor-like kinase

Abstract: Development in higher plants depends on the activity of meristems, formative regions that continuously initiate new organs at their flanks. Meristems must maintain a balance between stem cell renewal and organ initiation. In fasciated mutants, organ initiation fails to keep pace with meristem proliferation. The thick tassel dwarf1 (td1) mutation of maize affects both male and female inflorescence development. The female inflorescence, which results in the ear, is fasciated, with extra rows of kernels. The male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
253
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(259 citation statements)
references
References 50 publications
(50 reference statements)
4
253
0
2
Order By: Relevance
“…td1 and fea2 mutants show striking enlargement/fasciation of inflorescence meristems and an increase in spikelet density with occasional abnormal floral phenotypes, indicating that TD1 and FEA2 are negative regulators of the SAM, as in Arabidopsis (Bommert et al, 2005;TaguchiShiobara et al, 2001). TD1 transcripts are detected in the peripheral region of the maize vegetative SAM and in leaf primordia, but not in the CZ.…”
Section: Rlks In Other Plant Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…td1 and fea2 mutants show striking enlargement/fasciation of inflorescence meristems and an increase in spikelet density with occasional abnormal floral phenotypes, indicating that TD1 and FEA2 are negative regulators of the SAM, as in Arabidopsis (Bommert et al, 2005;TaguchiShiobara et al, 2001). TD1 transcripts are detected in the peripheral region of the maize vegetative SAM and in leaf primordia, but not in the CZ.…”
Section: Rlks In Other Plant Speciesmentioning
confidence: 99%
“…TD1 transcripts are detected in the peripheral region of the maize vegetative SAM and in leaf primordia, but not in the CZ. In inflorescences, however, TD1 is expressed throughout the outer cell layers of the inflorescence meristem and on its flanks at positions of spikelet pair meristem (SPM) initiation (Bommert et al, 2005). The implications of these changing expression patterns are unclear, since TD1 functions more specifically in the inflorescence meristem, and its vegetative function is not clear.…”
Section: Rlks In Other Plant Speciesmentioning
confidence: 99%
“…Upadyayula et al (2006) identified a set of QTL for tassel branch number, central spike spikelet pair density, kernel number density, kernel row number, kernel number per row, and cob diameter. Some of these parameters were co-located with genes that are known to affect the development of maize inflorescences, such as ramosa1 , ramosa2, thick tassel dwarf1 (Bommert et al, 2005), and fasciated ear2 (Taguchi-Shiobara et al, 2001); however, other genes in the QTL regions were unknown. We found that only a few cloned mutant genes were closely linked with the QTL detected for KRN in this investigation.…”
Section: Differences In Loci Controlling Natural Variation Of Krn Commentioning
confidence: 99%
“…Rice floral organ number1 ( fon1), fon2, and maize fascinated ear and thick tassel dwarf1, all defective in the CLAVATA signaling pathway, contain enlarged SAMs and exhibit abnormal branching patterns (Taguchi-Shiobara et al, 2001;Suzaki et al, 2004Suzaki et al, , 2006Bommert et al, 2005b;Chu et al, 2006). In contrast, the lonely guy (log) mutant that has a defect in synthesis of active cytokinins (CKs) has a small SAM and produces an inflorescence markedly reduced in size (Kurakawa et al, 2007).…”
mentioning
confidence: 99%